2016
DOI: 10.9734/ejmp/2016/26453
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products Screening for the Identification of Selective Monoamine Oxidase-B Inhibitors

Abstract: Aims Monoamine oxidase-B inhibitors (MAO-BIs) are used for the initial therapy of Parkinson’s disease. Also, MAO-BIs have shown to be effective neuroprotective agents in several neurodegenerative diseases. However, some concerns exist regarding the long-term use of these compounds. Meanwhile, natural compounds showed potential MAO-B selective inhibitions. To date, few selective natural MAO-BIs have been identified. Therefore, the current study is designed to identify plants with potent and specific MAO-B inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 67 publications
0
7
0
1
Order By: Relevance
“…The oleogum resin of F. assa-foetida also showed antioxidant, antiviral, antifungal, antispasmodic, and antihypertensive effects in pharmacological studies [ 90 ]. It has been documented that F. assa-foetida resin can potentially inhibit monoamine oxidase B (MAO-B), and it can be used in the therapy of neurodegenerative diseases such as Parkinson's and Alzheimer's diseases [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…The oleogum resin of F. assa-foetida also showed antioxidant, antiviral, antifungal, antispasmodic, and antihypertensive effects in pharmacological studies [ 90 ]. It has been documented that F. assa-foetida resin can potentially inhibit monoamine oxidase B (MAO-B), and it can be used in the therapy of neurodegenerative diseases such as Parkinson's and Alzheimer's diseases [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…The researchers stated that oleo gum-resin of asafoetida could improve renewal and re-myelination and declines the rate of lymphocyte penetration in the neuropathic muscle in rats; thus, its action as a neuroprotective and nerve simulative agent in peripheral neuropathy (37). It is scientifically proved that it can also use in the treatment of neurodegenerative ailments like Parkinson's and Alzheimer's diseases (38). In the behavioral model, inactive prevention test, the lesser quantity of extract (200 mg) cannot increase memory while in high quantity (400mg), it improved memory in Wistar rats (39).…”
Section: Ferula Asafoetidamentioning
confidence: 99%
“…It has also been documented that oleo gum resin of F. asafoetida can enhance regeneration and re-myelination and decreases the rat of lymphocyte infiltration in the neuropathic tissue in mice; therefore it acts as a neuroprotective and nerve simulative agent in peripheral neuropathy 64 . Scientific evidences have also shown that F. asafoetida resin can potentially inhibit monoamine oxidase B (MAO-B) and it can be used in the therapy of neurodegenerative diseases such as Parkinson ' s and Alzheimer's diseases 65 . Meanwhile, Ferula asafoetida has been reported to have acetylcholinestrase (AChE) inhibiting property in vitro assay and in vivo on snail nervous system.…”
Section: Neuroprotective Effects Of Medicinal Plantsmentioning
confidence: 99%
“… 64 Scientific evidences have also shown that F. asafoetida resin can potentially inhibit monoamine oxidase B (MAO-B) and it can be used in the therapy of neurodegenerative diseases such as Parkinson ' s and Alzheimer's diseases. 65 Meanwhile, Ferula asafoetida has been reported to have acetylcholinestrase (AChE) inhibiting property in vitro assay and in vivo on snail nervous system. Researchers have proposed that memory increasing effect of Ferula asafoetida could be attributed to inhibitory effect of this plant on AChE in the rat brain.…”
Section: Neuroprotective Effects Of Medicinal Plantsmentioning
confidence: 99%